1990
DOI: 10.1002/jlb.47.3.206
|View full text |Cite
|
Sign up to set email alerts
|

Differential Tumor Necrosis Factor Production by Human Monocyte Subsets

Abstract: The human monocyte (M phi subset rosetting with anti RH-coated human erythrocytes via high-affinity, 72 kD receptors (FcRI+), contains the PGE2-producing immunosuppressive subpopulation, while the non-rosetting M phi subset (FcRI-) is the major plasminogen activator-producing and antigen-presenting M phi. This study gives additional evidence for the functional disparity of the FcRI- and FcRI+ M phi subsets. We are demonstrating that the normal human M phi subset isolated by rosetting via the FcRI receptor (FcR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 37 publications
3
19
2
Order By: Relevance
“…Increased circulating CD64 ϩ inflammatory Macs have been previously described in injury, and these more inflammatory Mac have altered function (41, 44 -46). We have previously reported that trauma patient M with high CD64 expression produce exaggerated amounts of the 26-kDa, cell-associated form of TNF-␣ with increased TNF-␣ mRNA stability (1,47). A recent report describes hM-CSF-differentiated PBMC Mac as producing higher TNF levels than M because of their increased TNF mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…Increased circulating CD64 ϩ inflammatory Macs have been previously described in injury, and these more inflammatory Mac have altered function (41, 44 -46). We have previously reported that trauma patient M with high CD64 expression produce exaggerated amounts of the 26-kDa, cell-associated form of TNF-␣ with increased TNF-␣ mRNA stability (1,47). A recent report describes hM-CSF-differentiated PBMC Mac as producing higher TNF levels than M because of their increased TNF mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…38 Classical human monocytes are potent phagocytes 39 and produce higher amounts of cytokines like IL-6 and TNF. 40,41 In contrast, nonclassical monocytes are potent antigen-presenting cells. 42 Such distinct differences have not yet been described for the murine equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…This population of murine monocytes shares morphological characteristics and chemokine receptor expression patterns with the classical human CD14 hi CD16 -monocytes, and murine resident monocytes are thought to correspond to human CD14 ϩ CD16 ϩ nonclassical monocytes [34]. Human classical monocytes are potent phagocytes [37] and produce higher amounts of cytokines such as IL-6 and TNF-␣ [38,39]. In contrast, nonclassical monocytes are potent APC [40].…”
Section: Azurocidin Induces Recruitment Of Monocytesmentioning
confidence: 99%